Budget Management: A Key Lever for Strategic Decision-Making - Kohzad, Shahab (International Journal of Business Management and Entrepreneurship, 2024)
This article provides an in-depth analysis of the essential role of budgetary management as a classic management control tool while highlighting its significant implications in public and private organizations. By tracing its historical evolution from its origins in England to its widespread adoption in the private sector, the study demonstrates the growing importance of budgetary management as an essential instrument of strategic decision-making. The fundamentals of the budget system highlight the entire budget process, its alignment with organizational strategies, controllability, and its link to the decision-making system. Control by exception is a crucial approach for efficient budgetary management. As a strategic planning, coordination, and communication tool, it facilitates the achievement of organizational objectives. In addition, budget management acts as a powerful lever for controlling and monitoring achievements, allowing managers to make informed decisions. It also helps motivate and involve employees, thus promoting the company’s or public organization’s overall performance. By emphasizing that budgetary management is an essential management control tool, going far beyond its simple financial planning function. Its successful integration into the organization’s decision-making processes helps improve performance and achieve strategic objectives. Adopting appropriate budgeting methods is essential to maximize its effectiveness, ensuring efficient budget management and the achievement of organizational ambitions.